College student adaptation to childhood adversity: a model of stress and resilience - Cole, Megan Twomey, author; Rosen, Lee, advisor; Dik, Bryan, committee member; Swaim, Randall, committee member; Biringen, Zeynep, committee member (Colorado State University. Libraries, 2010)
A model of resilience was tested in a college sample of 672 students. Data were collected on the association of negative life events and college adjustment. The influence of Neuroticism, coping style, and social/emotional resources was also studied. Structural equation modeling procedures were used to analyze these data, and a moderating effect of gender was hypothesized. Results provided support for the hypothesized model and indicated that stress, Neuroticism, Engagement coping, and social/emotional resources have important implications for adjustment. Specifically, it was found that the experience of negative life events was positively associated with elevated levels of Neuroticism for both men and women. Neuroticism, in turn, was associated with Disengagement coping as well as a decrease in social/emotional resource availability. Neuroticism was also negatively associated with college adjustment, though Neuroticism was somewhat more strongly related to college adjustment for females. Coping styles were also related to the availability of social/emotional resources, such that the use of Engagement coping was associated with greater resource availability. Furthermore, results indicated the presence of a positive relationship between Engagement coping and college adjustment, whereas no relationship was observed between college adjustment and Disengagement coping. Surprisingly, results suggested the presence of no relationship between /emotional resources and adjustment to college. Additional analyses examined social the relationship between life events and adjustment, and it was found that those disproportionately experiencing more negative life events reported poorer college adjustment. Possible explanations for the observed findings are considered. Implications for practice are discussed.
Covers not scanned.
Keywords: Personality and academic achievement; Resilience (Personality trait); Neuroses